Heart and skeletal muscle inflammation – novel dangerous disease of farmed Salmonidae - V. P. Melnikov; V. V. Pronin (Ветеринария сегодня)
Heart and skeletal muscle inflammation (HSMI) is one of the most widespread economically relevant diseases of farmed Atlantic salmon (Salmo salar), and it poses serious danger to its aquaculture. The disease was first reported in Norway in 1999. In 2006, the Norwegian researchers demonstrated its viral etiology. Heart and skeletal muscle inflammation is a novel and understudied highly contagious transboundary disease of Salmonidae characterized by erythrocyte damage, blood circulation failure, jaundice and aggregated signs of heart and skeletal muscle inflammation. The disease associated economic damage to aquaculture is enormous. Total cumulative mortality can reach 30% and morbidity can amount to 100%. Loss of quality of the commercial fish products due to melanised foci in the salmons’ muscles further increases the disease-associated economic losses. Aquacultured Atlantic salmon is the most susceptible to HSMI. Rainbow trout, chub salmon and bull trout are also susceptible species and the list is still being continued. The disease is caused by the virus belonging to genus Orthoreovirus in the family Reoviridae. Currently Piscine orthoreovirus demonstrates the tendency towards its global spread. The virus-induced disease is reported in Norway, Scotland, Ireland, Iceland, France, Germany, Italy, Denmark and Alaska. The majority of the outbreaks are registered in Central and Northern parts of Norway, which borders the Murmansk Oblast. The vicinity of the affected areas to Russia, the Gulf Stream passing the Norwegian shore while moving towards the Murmansk Oblast as well as wild Salmonidae migration to the Barents Sea, White Sea and Pechora Sea through the Norwegian territorial waters coupled with high stability of the virus compose high threat of Piscine orthoreovirus introduction to the Russian Federation from the adjacent countries.